Health Insurance Coverage for Vulnerable Populations: Contrasting Asian Americans and Latinos in the United States - Margarita Alegría; Zhun Cao; Thomas G. McGuire; Victoria D. Ojeda; Bill Sribney; Meghan Woo; David Takeuchi (SAGE Publishing, 2006)
This paper examines the role that population vulnerabilities play in insurance coverage for a representative sample of Latinos and Asians in the United States. Using data from the National Latino and Asian American Study (NLAAS), these analyses compare coverage differences among and within ethnic subgroups, across states and regions, among types of occupations, and among those with or without English language proficiency. Extensive differences exist in coverage between Latinos and Asians, with Latinos more likely to be uninsured. Potential explanations include the type of occupations available to Latinos and Asians, reforms in immigration laws, length of time in the United States, and regional differences in safety-net coverage. Policy implications are discussed.